2019
DOI: 10.18632/oncotarget.27152
|View full text |Cite
|
Sign up to set email alerts
|

Safety evaluation of conditionally immortalized cells for renal replacement therapy

Abstract: End-stage kidney disease represents irreversible kidney failure. Dialysis and transplantation, two main treatment options currently available, present various drawbacks and complications. Innovative cell-based therapies, such as a bioartificial kidney, have not reached the clinic yet, mostly due to safety and/or functional issues. Here, we assessed the safety of conditionally immortalized proximal tubule epithelial cells (ciPTECs) for bioartificial kidney application, by using in vitro a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 71 publications
2
8
0
Order By: Relevance
“…In addition, after an inflammatory insult (exposure to lipopolysaccharide and IFN-γ), we found increased, polarized secretion of pro-inflammatory cytokines into the extra luminal (filtrate) space compared with the intraluminal (blood) space, indicating the immunological safety of the system 103 . We also showed that ciPTECs do not exhibit tumorigenic and/or oncogenic potential in vitro or in vivo 106 . Current challenges for this system are upscaling the BAK to a clinically relevant size and developing a production process that would make the device affordable for maintenance dialysis.…”
Section: Bioartificial Kidney Systemssupporting
confidence: 52%
“…In addition, after an inflammatory insult (exposure to lipopolysaccharide and IFN-γ), we found increased, polarized secretion of pro-inflammatory cytokines into the extra luminal (filtrate) space compared with the intraluminal (blood) space, indicating the immunological safety of the system 103 . We also showed that ciPTECs do not exhibit tumorigenic and/or oncogenic potential in vitro or in vivo 106 . Current challenges for this system are upscaling the BAK to a clinically relevant size and developing a production process that would make the device affordable for maintenance dialysis.…”
Section: Bioartificial Kidney Systemssupporting
confidence: 52%
“…Silencing LaminB1 immediately leads to inhibition of proliferation and the induction of senescence ( Shimi et al, 2011 ). Our previous research regarding cell cycle analysis of ciPTEC-OAT1 at permissive and non-permissive temperatures ( Mihajlovic et al, 2019 ) has shown that ciPTEC-OAT1 when cultured at 37°C for 1 or 7 d exhibits significantly reduced proliferation (less cells in the S phase) and an increased number of cells in the G0/G1 phase of the cell cycle, indicating halted proliferation at a non-permissive temperature. This is in line with our current results.…”
Section: Discussionmentioning
confidence: 99%
“…Baseline levels of injury marker KIM-1 were 20-fold higher in immortalized cells compared to primary cells (Sakolish et al 2018). In addition, immortalized cell lines often show chromosomal instability, as demonstrated for ciPTEC-OAT1 without affecting cell function or posing a tumorigenic risk (Mihajlovic et al 2019), and represent a homogenous population instead of a genetic diverse population. Therefore, new sources for kidney cells emerged in the past decade.…”
Section: Perspectives In In Vitro Models' Developmentmentioning
confidence: 97%